ANALISIS RUGI – RUGI DAYA DAN JATUH TEGANGAN UNTUK REKONFIGURASI PENYULANG RWO 05 DAN RWO 07 GARDU INDUK RAWALO MENGGUNAKAN ETAP 12.6 DAN MATLAB R2018a - Della Prastika Haris Sasmita; Hermawan Hermawan; Susatyo Handoko (Transient: Jurnal Ilmiah Teknik Elektro, 2020)
The need for electrical energy which always rises causes an increase in the loading of each feeder in Rawalo Substation. PT. PLN (Persero) UP3 Purwokerto strives to carry out a reconfiguration on RWO 05 and RWO 07 feeder in order to decrease the load in RWO 05 feeder so that the electrical energy distributed to the consumers can be optimized. The distribution of electrical energy cannot be separated from the loss of power in the system which causes the disappearance of numbers of power in the electrical energy distribution process, starting from the main substation to the consumers. Therefore, there has to be an analysis done about power loss and voltage drop which occurs in the distribution networks by configuring one out of four switches in a normally open condition that connects RWO 05 and RWO 07, not only in an existing condition but also after the reconfiguration being done. Based on the result of the analysis, the power loss occurred in an existing condition which is in switch 2 holds the amount of 0,137 MW and 0,436 MVAR or equal to 2,18 % with the amount of 6,58% voltage drop, while the power loss occurred in a reconfiguration condition which is in switch 4 holds the amount of 0,116 MW and 0,385 MVAR or equal to 1,84 % with the amount of 6,13% voltage drop. The result of the loss obtained from both conditions concludes that there is a decrease in power loss with the amount of 0,33 %, whereas the voltage drop occurred decreases by 0,45%.